Harming by Deceit: Epistemic Malevolence and Organizational Wrongdoing - Marco Meyer; Chun Wei Choo (Journal of Business Ethics, 2023)
Research on organizational epistemic vice alleges that some organizations are epistemically malevolent, i.e. they habitually harm others by deceiving them. Yet, there is a lack of empirical research on epistemic malevolence. We connect the discussion of epistemic malevolence to the empirical literature on organizational deception. The existing empirical literature does not pay sufficient attention to the impact of an organization's ability to control compromising information on its deception strategy. We address this gap by studying eighty high-penalty corporate misconduct cases between 2000 and 2020 in the United States. We find that organizations use two different strategies to deceive: Organizations 'sow doubt' when they contest information about them or their impacts that others have access to. By contrast, organizations 'exploit trust' when they deceive others by obfuscating, concealing, or falsifying information that they themselves control. While previous research has focused on cases of 'sowing doubt', we find that organizations 'exploit trust' in the majority of cases that we studied. This has important policy implications because the strategy of 'exploiting trust' calls for a different response from regulators and organizations than the strategy of 'sowing doubt'.
Keywords: 300; Epistemic vice; Organizational wrongdoing; Epistemic malevolence; Deception; Organizational behavior